Penentuan Indeks Seleksi untuk Galur Dihaploid Padi Sawah Tadah Hujan Berdaya Hasil Tinggi - Akbar, Miftahur Rizqi; Purwoko, Bambang Sapta; Dewi, Iswari Saraswati; Suwarno, Willy Bayuardi; Sugiyanta, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Rainfed rice breeding for high yield is an alternative to increase national rice production. The breeding can beaccelerated using anther culture technique. The selection of high productivity lines may be more effective if it also involvesthe traits contributing to or affecting the yield traits. This study aimed at determining suitable characters as selection criteriaand obtain a selection index model for high yielding doubled haploid rainfed rice lines. The experiment was conductedin a greenhouse of ICABOGRAD, Bogor and Sawah Baru Experimental Station, Bogor Agricultural University using arandomized complete block design (RCBD) with three replications. Thirty doubled haploid lines derived from anther cultureand two check varieties namely Ciherang and Inpari 18 were used. The results showed that plant height (TT), number of filledgrain per panicle (GI), and productivity (PRD) could be used as suitable selection characters. The determination of selectionindex obtained a selection model which was Selection index = 0.48 PRD + 0.31 JGI - 0.31 TT. This model can be used toselect high yielding doubled haploid rainfed rice lines.